Controls on cobalt concentrations in ferromanganese crusts from the Magellan seamounts, west Pacific - Xiangwen Ren; Xiangwen Ren; James R. Hein; Zanzhong Yang; Na Xing; Aimei Zhu (Frontiers in Marine Science, 2024)
IntroductionCobalt is the most important critical element in ferromanganese crusts. Co concentration in the Fe-Mn crusts is one of the key parameters for determination of the Co resource. Thus, it is essential to clarify the controls on the variations of Co concentration of ferromanganese crusts.MethodsTo clarify the controls on Co concentration of hydrogenetic nonphosphatized ferromanganese crusts, an equation was deduced based on Fick’s First Law: Co(%)=Mn02(%)·Dsw·cswδ·zGR·Ssp, and eight potential controls were gleaned from this equation, including dilution, diffusivity of Co ions in seawater (Dsw), temperature which controls the Dsw, Co ion concentration in seawater (Csw), the diffusion distance of Co ions near the interface of seawater and Fe-Mn crusts (δ), thickness of one molecular layer (z), growth rate (GR), and specific surface area of Fe-Mn crusts (Ssp). To constrain the value of Co ion diffusion gradients (Csw¯/δ) and consequently verify the proposed equation, we determined the Co concentrations, growth rates, and specific surface area of the outermost layer of Fe-Mn crusts, and calculated diffusivity of Co2+.ResultsThe Csw¯/δ for the Fe-Mn crusts from Caiwei seamount (Magellan seamounts) was determined to be 295-496 pM/mm, which are reasonable for the Co ion concentrations and seawater mixing in the deep ocean.DiscussionAccording to the equation established in this study, the trend of decreasing Co concentrations in Fe-Mn crusts with increasing water depth is controlled mainly by dilution and to a lesser extent by seawater Co ion concentration, temperature of seawater, and consequently the diffusivity of Co ions in seawater.